Zinc: A Critical Micronutrient for Children’s Health - Luiz Antonio Del Ciampo; Ieda Regina Lopes Del Ciampo (Archives of Current Research International, 2024)
Zinc is one of the most abundant micronutrients in the human body, found in all tissues and playing an important role in vital structural, regulatory, hormonal and catalytic functions. Zinc deficiency is a major public health problem that affects almost one fifth of the world’s population, being more common in low-income countries, where diets are poor in zinc sources, impacting morbidity and mortality rates, especially among children under five years of age. This narrative review updates the state of the art on the subject, highlighting the importance of zinc for metabolism, its metabolic roles and absorption issues, the clinical repercussions of deficiency conditions among children and points out some actions that can be implemented to reduce the severity of the problem, like supplementation, fortification, and biofortification that are proposed to mitigate zinc deficiency.